Cyberbullying : causes, consequences, and coping strategies - Weber, Nicole L. (Criminal justice (LFB Scholarly Publishing LLC), 2014)
Weber and Pelfrey examine qualitative and quantitative data collected from middle and high school students in a large urban area regarding the use of social technologies in cyberbullying perpetration and victimization. They further explore the interconnectedness between the online and face-to-face environments created by these advancements in technology which may produce risk taking behaviors and school safety issues. Students reported a carryover between environments (during school and after school via social technology) that create a constant access to peers and a reciprocal relationship bet.